META-ANALYSIS STUDY OF THE EFFECT OF GUIDED INQUIRY MODEL ON CRITICAL THINKING SKILLS OF STUDENTS SCIENCE CONCEPTS - Sari, Nurmala; Istiyono, Edi; Purbani, Widyastuti; Retnawati, Heri (Universitas Tanjungpura, 2023)
The development of education in the 21st century requires educators and students to be able to improve critical thinking skills. The process of improving critical thinking skills requires a learning model, one of which is through a guided inquiry model. The application of the inquiry model is able to train students to have the ability to think about something new so that they can solve students' own concepts or ideas. The purpose of this study was to analyze the effect of the guided inquiry model on students' critical thinking skills. Data collection techniques were carried out by browsing various articles related to the inquiry model and critical thinking skills through Google, Google Scholar, and Scopus. The search results obtained 35 articles or related journals. Data analysis technique was carried out in a quantitative descriptive manner using the help of Microsoft Excel and JASP applications. The results showed that the results of the analysis using the random effect had a significant positive effect or correlation between the guided inquiry model on students' critical thinking skills in science lessons. The results of the egger test and fail safe N analysis show that there is no publication bias in the meta-analytical studies discussed, so that the analyzed meta-analytical studies can be scientifically justified.